Pengaruh Model Kooperatif Two Stay Two Stray Terhadap Hasil Belajar PKN Siswa Kelas V Sekolah Dasar - Fitri, Asnita El; Reinita, Reinita; Mayarnimar, Mayarnimar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2015)
This study aims to determine the effect of the cooperative model of Two Stay Two Stray on the learning outcomes of class V Civics of SDN Gugus I Sintoga District, Padang Pariaman Regency . This research is a quantitative research with experimental research methods. The sample in this study consisted of experimental group which amounted to 20 students and control groups totaling 20 students, with a population of 122 people. The instrument used in collecting data is in the form of tests with multiple choice types. The results of the research that have been analyzed, obtained t count > t table is 3.03 > 1.68595 with α = 0.05 which means Ho is rejected and Ha is accepted. So that it can be concluded that there is the effect of the cooperative model Two Stay T wo Stray ( TSTS ) on the learning outcomes of class V Civics of SDN Gugus I Sintoga District, Padang Pariaman Regency. keywords: two stay two stray , pkn